Geopolymers as active capping materials for in situ remediation of metal(loid)-contaminated lake sediments. Issue 1 (February 2019) - Kutuniva, Johanna; Mäkinen, Jari; Kauppila, Tommi; Karppinen, Anssi; Hellsten, Seppo; Luukkonen, Tero; Lassi, Ulla
Graphical abstract: Highlights: Geopolymers are novel active capping materials for contaminated sediments. Metal(loid) bioavailability decreased compared to unamented sediment. Slag-based geopolymer was more effective than metakaolin geopolymer or vermiculite. The overall best material, alkali-activated slag, was suitable for Al, Cu, Fe and Ni. Metakaolin geopolymer was suitable for Cu, Cr, and Fe and vermiculite for Al and Zn. Abstract: Metal(loid) contamination in sediments is a widespread environmental issue. Sediments act normally as metal(loid) sinks, but if chemical conditions (such as pH or redox potential) change, they can become sources of secondary pollution. Consequently, various strategies for both in and ex situ remediation of contaminated sediments have been developed. One promising method is active capping, which involves the injection of adsorbents as a layer on the sediment surface or the mixing of adsorbents within the sediment. Adsorbents decrease the bioavailability of metal(loid)s. In the present work, the suitability of alkali-activated blast-furnace-slag, metakaolin geopolymer, and exfoliated vermiculite were evaluated for in situ stabilization of two metal(loid)-contaminated lake sediments through laboratory-scale experiments. The results indicated that adsorbent amendments had metal(loid)-specific performance: alkali-activated blast-furnace slag was suitable for Al, Cu, Fe, and Ni; metakaolin geopolymer for Cu, Cr (total), and Fe; and vermiculite for Al and Zn. None of the materials could stabilize Ba, Sr, or Ti. Furthermore, the amendments performed differently in two different lake sediments, implying that the effectiveness of the amendments needs to be confirmed on a case-by-case basis.